IAPSM’s Textbook of Community Medicine - Barwal, Vijay Kumar; Sharma, Gopal Ashish (International Journal Of Community Medicine And Public Health, 2019)
A great effort by the editor-in-chief, Dr. A. M. Kadri, a well-known academician and teacher as well as the secretary general of IAPSM for more than three years, to compile the work of over 200 authors who are subject experts and teachers of Community Medicine from all over India. This book exhibits expertise of the subject from every nook and corner of India. It is nicely framed and the font size, print, tables, diagrams are reader friendly and pleasing to the eyes.